2023
DOI: 10.35848/1347-4065/ace5b6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mn doping on the ferroelectric photovoltaic effect in multidomain BiFeO3 thin films under above-bandgap illumination

Abstract: While recent studies have revealed that chemical doping can enhance the photovoltaic (PV) response of ferroelectrics under light with photon energy (hν) lower than the bandgap energy (E g), its impact under above-bandgap illumination (hν > E g) is not fully understood. In this study, the PV response at hν > E g of Mn-doped BiFeO3 (BFO) thin films with a periodic stripe domain pattern is investigated. The short-circuit photocurrent density (J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…This may be caused by the domination of the oxygen vacancies with an increase in the Mn amount, as shown in Figure 4d, which was reported to increase the recombination rate of photo-generated carriers [18]. Matsuo et al reported that the local electric field across the domain walls of BFO films could be suppressed by Mn doping due to a screening effect by charged defects [33].…”
Section: Resultsmentioning
confidence: 91%
“…This may be caused by the domination of the oxygen vacancies with an increase in the Mn amount, as shown in Figure 4d, which was reported to increase the recombination rate of photo-generated carriers [18]. Matsuo et al reported that the local electric field across the domain walls of BFO films could be suppressed by Mn doping due to a screening effect by charged defects [33].…”
Section: Resultsmentioning
confidence: 91%
“…92) Owning to its attractive features, many researchers have investigated the ferroelectric, 93,94) magnetic, [95][96][97] piezoelectric, [98][99][100][101] capacitive, 102) and structural [103][104][105][106] properties of BFO and its solid solutions. The relatively small E g coexisting with the massive P s has motivated us to investigate their fundamental PV properties 4,16,22,56,107,108) and to develop PV devices. Ji et al 54) demonstrated the bulk PV effect by measuring the light polarization angle dependence of photocurrent flowing perpendicular to P s for (111)oriented BFO epitaxial thin films on STO substrates.…”
Section: Methodsmentioning
confidence: 99%